A feast of metaphor researchers, or RaAM in Sardinia - Šeškauskienė, Inesa (Taikomoji kalbotyra, 2014)
This is an overview of the 10th conference of the Association Researching and Applying Metaphor held in Cagliari, Sardinia, in June 2014.